Quantitative techniques (Vikas, 2013)
Managers in all types of Business organizations whether private or public sector, manufacturing or service industry- have to take decisions on how best to allocate their resources. These decisions are made on the basis of information obtained using statistical and decision making techniques. quantitative techniques are powerful tools using which production can be augmented, profit maximized , cost maximized and production methods oriented for the accomplishment of certain predetermined objective. Now a days there is a growing tendency to turn to quantitative techniques as a mean for solving many of the problems that arise in a business or industrial enterprise. Quantitative techniques provides the decision maker with a systematic and powerful means of analysis, based on quantitative data, to explore policies and achieve predetermined goals. This book, Quantitative techniques, provides a basic understanding of these techniques that are particularly relevant to problems of complex business enterprises